A Review on characterization and application of fly ash cenosphere. Issue 1 (March 2021) - Gupta, T; Bokare, P S
Abstract: The Fly Ash Cenospheres (FAC) or alumino-silicate is one of the most valuable by-products of fly ash generated by coal thermal power plants. It is an industrial by-product of high commercial value. It is found that FAC is hollow spherical microspheres having sizes varying 5-500 µm and chemically inert particles and make them an ideal material to replace fine aggregate from cement concrete. This study presents a systematic review of observational studies on the properties and application of FAC. Different industries use FACs due to their unique properties such as hollow spherical shape and lightweight, less specific gravity, high compressive strength, high thermal resistance, and acoustic insulation, etc. The addition of FAC to concrete has found to reduce the density of concrete without compromising the strength. Other properties such as compressive strength, flexural strength, toughness, ductility, micro-structure, etc are also documented in this study. The gap in the literature is identified and reported at the end of the research report.